Perception of the Muslim Community of Blitar City on Large Scale Social Restrictions (PSBB) in the Time of the Covid-19 Pandemic - Kasiani, Kasiani; Evendi, Farkhan (Politeknik Harapan Bangsa Surakarta, 2021)
The current Covid-19 pandemic has become a global epidemic that allows anyone to be exposed regardless of nation, ethnicity and religion. The implementation of Large-Scale Social Restrictions (PSBB), which is an effort to break the chain of distribution, cannot be said to be a powerful solution to overcome the epidemic situation that makes all aspects of life difficult. This article focuses on how the Muslim community of Blitar City perceives PSBB during the Covid-19 Pandemic, especially with regard to the potential benefits and disadvantages. The method is a qualitative research and is a legal research with a normative-juridical pattern with empirical data obtained from several academic literatures on PSBB and its dynamics. The results show that PSBB in the midst of its complexity, has the opportunity to break and anticipate the spread of Covid-19 on the one hand, and has the power to weaken economic resilience on the other, thus triggering stakeholders to innovate to find solutions. This reality makes the Muslim community of Blitar City create several social movements based on food security, and maintain purchasing power.